Hubungan Pengetahuan Ibu Bersalin dengan Intensitas Nyeri persalinan Kala I Fase aktif - Ari Andayani; Tya Lestari (Universitas Ngudi Waluyo, 2021)
Pain during childbirth is a physiological condition, but if left untreated, labor pain will cause stress which can trigger the release of the hormone ketocolamine and steroids. This pain during labor is due to uterine contractions and the development / dilation of the cervix. The stronger the pain, the longer the peak pain will be during the active phase. The results of preliminary studies in August, 100% of mothers who gave birth felt pain and screaming at the time of delivery. The purpose of this study was to determine the relationship between maternal knowledge about labor pain and the intensity of labor pain during the first active phase.This study used quantitative descriptive research methods and data analysis used the chi squre test. The number of samples of 38 pregnant women in September - December 2020, the technique used was the total sampling technique. Data analysis with chi squre test. The results of the Chi Squre test showed a significant relationship between knowledge and the intensity of first stage labor pain (p value: 0.001). The Conclusion there is a relationship between knowledge about labor pain and the intensity of labor pain during the first stage.